Selling your expertise : the mindset, strategies, and tactics of successful rainmakers - Chen, Robert (Executive Coach) (Wiley, 2022)
"In this book Chen offers guidance to "knowledge professionals" on how to sell their ideas and expertise. Knowledge professionals include investment bankers, consultants, lawyers, accountants, scientists, and anyone else who needs to develop business by selling a service. The content will be supported by his experience and supplemented by scientific research. The book will be divided into 3 main sections: Mindset, Strategy & Tactics, and Measuring Success."--